Mobile Usage Behavior among Agricultural Students in Haryana - Malik, Anil Kumar; Yadav, Krishan; Yadav, V.P.S. (Indian Journal of Extension Education, 2021)
Mobile is a versatile technological tool used by the students for multiple purposes especially during COVID 19 pandemic viz., communication, education, research and entertainment. A study was carried out to assess the mobile usage behavior among the students of Chaudhary Charan Singh (CCS) Haryana Agricultural University, Hisar. Empirical data were collected personally from 200 students through a structured interview schedule and analyzed using standard methodology. Findings revealed that all the students used mobile daily for more than 4 hours. More than half of the students (54.00%) used Xiaomi/MI mobile phone with Jio network services for entertainment and communication purpose compared to academic and professional purpose. Social networking apps were most frequently visited by the students followed by entertainment and educational apps. Study also revealed that personality traits viz.; age, education, medium of schooling, schooling, annual expenditure, scientific orientation, mass media exposure, information seeking behavior and risk orientation exhibited positive and significant correlation with their usage behavior of mobile at 0.05 level of probability.
Keywords: Agricultural students; COVID-19; Mobile usage behavior; Technology integration